Venoarterial extracorporeal membrane oxygenation for postcardiotomy cardiogenic shock—A six‐year service evaluation. Issue 7 (23rd February 2020) - Charlesworth, Michael; Garcia, Miguel; Head, Laura; Barker, Julian M.; Ashworth, Alan D.; Barnard, James B.; Feddy, Lee; Venkateswaran, Rajamiyer V.
Abstract: Only a small number of English hospitals provide postcardiotomy venoarterial extracorporeal membrane oxygenation (VA‐ECMO) and there are doubts about its efficacy and safety. The aim of this service evaluation was to determine local survival rates and report on patient demographics. This was a retrospective service evaluation of prospectively recorded routine clinical data from a tertiary cardiothoracic center in the United Kingdom offering services including cardiac and thoracic surgery, heart and lung transplantation, venovenous extracorporeal membrane oxygenation (VV‐ECMO) for respiratory failure, and all types of mechanical circulatory support. In six years, 39 patients were supported with VA‐ECMO for refractory postcardiotomy cardiogenic shock (PCCS). We analyzed survival data and looked for associations between survival rates and patient characteristics. The intervention was venoarterial‐ECMO in patients with PCCS either following weaning from cardiopulmonary bypass or following a trial of inotropes and intra‐aortic balloon counterpulsation on the intensive care unit. 30‐day, hospital discharge, 1‐year and 2‐year survivals were 51.3%, 41%, 37.5%, and 38.5%, respectively. The median (IQR [range]) duration of support was 6 (4‐9 [1‐35]) days. Nonsurvival was associated with advanced age, shorter intensive care length of stay, and the requirement for postoperative hemofiltration. Reasonable survival rates can be achieved in selected patients who may have been expected to have a worse mortality without VA‐ECMO. We suggest postoperative VA‐ECMO should be available to all patients undergoing cardiac surgery be it in their own center or through an established pathway to a specialist center.